Molecular analysis of genomic changes in synthetic autotetraploid Phlox drummondii Hook. (24th September 2013) - Dar, Tanvir H.; Raina, Soom N.; Goel, Shailendra
<x xml:space="preserve">Abstract</x> Polyploidization is a major force that has shaped the evolution of flowering plants. Newly‐generated polyploids have been used to investigate the changes that occur in genomes immediately after polyploidization. The present research programme created colchitetraploids in Phlox drummondii and followed them through different generations (C0, C1, C2, and C3) to determine genomic changes. Genomic changes that followed autopolyploidization were investigated using amplified fragment length polymorphism (AFLP) and methylation‐sensitive amplified polymorphism (MSAP) technologies. The markers for which variation was evident were characterized by cloning and sequencing. Dot‐blotting was used to confirm increased or decreased abundance of the fragments for which variation was noted. We used bisulfite sequencing to determine changes in the levels of DNA methylation in the vicinities of the fragments that show variation. Our data indicate that these areas were more methylated in C2 and C3 colchitetraploids than in C0 and C1 colchitetraploids. The overall levels of methylation polymorphism found in C2 and C3 colchitetraploids were 1.0% and 1.65%, respectively. Changes were observed in both coding and noncoding regions. Some MSAP fragments that showed variation were similar to retrotransposons. Bisulfite sequencing indicated that CHH sites accounted for all the observed variation, whereas CG and CHG did not show any variation. The present study suggests that the genomic changes that accompany polyploidization in synthetic autopolyploids resemble those in allopolyploids. However, the extent of variation is lower in synthetic autopolyploids than in allopolyploids. These changes may help in the stabilization of the genomes of neo‐autopolyploids. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 591–605.